2017
DOI: 10.3390/f8090330
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Juniperus thurifera to Sequester Carbon in Semi-Arid Forest Soil in Spain

Abstract: Abstract:The main purpose of this work is to show the influence of vegetation in the storage and stabilisation of organic carbon in semi-arid Juniperus thurifera (J. thurifera) forest soil in central Spain. The variability of the organic matter storage with factors such as sex, trunk diameter and the protection of the canopy of the tree has been analysed. The distribution of the soil organic carbon (SOC) into different fractions has also been determined, in order to estimate the stability of the organic matter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…In accordance with other forest ecosystem studies 27,28 , this study showed that SOC generally decreased with increased soil depth. SOC in the 0–0.1 m soil layer was the highest in each age group because this layer incorporated ground litter and created organic matter through bioturbation 27 , whereas, at a depth of 0.4–0.6 m, there was a significantly lower level of SOC (Table 1) due to root distribution 29 .…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with other forest ecosystem studies 27,28 , this study showed that SOC generally decreased with increased soil depth. SOC in the 0–0.1 m soil layer was the highest in each age group because this layer incorporated ground litter and created organic matter through bioturbation 27 , whereas, at a depth of 0.4–0.6 m, there was a significantly lower level of SOC (Table 1) due to root distribution 29 .…”
Section: Discussionsupporting
confidence: 92%
“…present in Portugal and Spain. In fact, this kind of habitat-among others-could also sequester a substantial amount of CO 2 , as in the case of the juniper forest in Central Spain, which is characterised by other species of Juniperus such as J. thurifera L. and J. communis L. [71]. It is today essential to develop a modern forest management system in protected areas, and to promote the importance of forests and their extensions as a means of protecting and improving the natural environment, according to Rădulescu et al [72].…”
Section: Discussionmentioning
confidence: 99%
“…Western North America, Central Asia and Australia all have large areas of semi‐arid woodlands and forests (Cherlet et al, 2018 ) and numerous authors have drawn attention to the potential losses of carbon, habitat and local livelihoods that could stem from their degradation (e.g. Charro et al, 2017 ; Trumper et al, 2008 ; Werneck et al, 2012 ). Long‐term data revealed contrasting changes in carbon accumulation in semi‐arid Miombo woodlands, with gains in regrowth and losses in old‐growth stands, due to fire and harvesting (Chidumayo, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Western North America, Central Asia and Australia all have large areas of semi-arid woodlands and forests (Cherlet et al, 2018) and numerous authors have drawn attention to the potential losses of carbon, habitat and local livelihoods that could stem from their degradation (e.g. Charro et al, 2017;Trumper et al, 2008;Werneck et al, 2012).…”
Section: Stability Of Semi-arid Forests Assessed Using Long-term Datamentioning
confidence: 99%